Don't fail to plan for summer reading interventions. Issue 3 (4th May 2020) - Reed, Deborah K.; Gates, Carly
Abstract: Summer reading programs are a common means of providing wraparound services to improve the performance of students' with or at risk for reading disabilities. Today's programs are not merely camps but are complex and costly academic efforts that require year-round planning to be successful. School personnel responsible for these programs typically have other full-time roles within the district, so this article offers guidance on the planning steps to take in fall, winter, and spring as well as during the summer. Examples of decisions to make, steps to take each month, and budget components are provided.